Non-Coding RNAs Associated With Radioresistance in Triple-Negative Breast Cancer - Aranza-Martínez, Alberto; Sánchez-Pérez, Julio; Brito-Elias, Luis; López-Camarillo, César; Cantú de León, David; Pérez-Plasencia, Carlos; López-Urrutia, Eduardo (Frontiers in Oncology, 2021)
The resistance that Triple-Negative Breast Cancer (TNBC), the most aggressive breast cancer subtype, develops against radiotherapy is a complex phenomenon that involves several regulators of cell metabolism and gene expression; understanding it profoundly is the only way of overcoming it. We focused this review on the contribution of the two leading classes of regulatory non-coding RNAs, microRNAs (miRNAs) and long non-coding RNAs (lncRNAs) against ionizing radiation-based therapies. We found that these regulatory RNAs are mainly associated with DNA damage response, cell death and cell cycle regulation, although they are reported to regulate other processes such as cell signaling and metabolism. Several regulatory RNAs regulate multiple pathways simultaneously, such as miR-139-5p, the miR-15 family, and the lncRNA HOTAIR. On the other hand, proteins such as CHK1 and WEE1 are targeted by several regulatory RNAs at the same time. Interestingly, the study of miRNA/lncRNA/mRNA regulation axes is increasing, opening new avenues for understanding radioresistance. Many of the miRNAs and lncRNAs that we reviewed here can be used as molecular markers or targeted by upcoming therapeutic options, undoubtedly contributing to better prognosis for TNBC patients. We live in a very exciting time in non-coding RNA research.